Understanding consumer decision making in grocery markets: new evidence from the Fishbein model - Knox, Simon (Cranfield University, 1996)
The paper reports on an empirical study of purchase decision making in grocery markets. Against the central research question, “Does decision making become more extensive with more involving product purchases?“, measurements of attitudebehaviour consistency were made in three product fields which are known to engender significantly different levels of consumer involvement. The Extended Fishbein Model was used as the metaphor for decision making and models were estimated for each product field using LISREL VII to determine the fit between product and normative beliefs, behavioural intention and actual purchasing behaviours. The results for our analysis are consistent with prior theory and support the hypothesis that the efficacy of the model in grocery markets increases as purchase involvement increases. The practical implications for marketing management competing in each market are discussed and the limitations of our research design are highlighted.